Shuna's journey - Miyazaki, Hayao, 1941- (First Second, 2022)
Shuna, the prince of a poor country, watches as his people toil to grow grain that barely feeds them. When he's given a handful of golden seeds from a traveler, he sets out towards the western lands, hoping to procure enough of the grain to feed his people. The journey is long and arduous and the people he meets are cruel. Along the way, he helps free a proud and stubborn girl named Thea and her sister, who later become his saviors when he runs into trouble after finally reaching the Land of the God-Folk.